2012
DOI: 10.3171/2011.10.peds11102
|View full text |Cite
|
Sign up to set email alerts
|

Gross and microscopic study of the filum terminale: does the filum contain functional neural elements?

Abstract: Object The filum terminale (FT) is considered a fibrous structure that extends from conus medullaris of the spinal cord to coccyx. Based on previous studies and from their own experience with intraoperative electrophysiological monitoring of the sacral nervous system, the authors postulate that the FT contains functional neural elements in some individuals. Methods The FT was dissected from 13 fresh stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Various studies have demonstrated abundance of collagen and elastic fibres, as well as undifferentiated, progenitor cells or multipotent precursors, explaining, according to some authors, the occurrence of ependymal tumours or teratoma at that level [14][15][16]. In particular Tubbs et al [17] described the presence of smooth muscle, nerve, bone, cartilage and adipose tissue in samples from cadaveric filum externa.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated abundance of collagen and elastic fibres, as well as undifferentiated, progenitor cells or multipotent precursors, explaining, according to some authors, the occurrence of ependymal tumours or teratoma at that level [14][15][16]. In particular Tubbs et al [17] described the presence of smooth muscle, nerve, bone, cartilage and adipose tissue in samples from cadaveric filum externa.…”
Section: Discussionmentioning
confidence: 99%
“…Gaddam et al [5] found the following 2 types of spinal nerve roots in and along the filum in stillborn cadavers (36 weeks): (1) a nerve traversing within the filum terminale and (2) a nerve attaching to and running along the filum. Kural et al [6] also reported demyelinated nerve fascicles with epineurium and ganglion cells in 34% of 14- to 35-week fetal specimens.…”
Section: Discussionmentioning
confidence: 99%
“…For this to be the case, conversely, a remnant of neural cells is likely to persist into later development and growth. However, the classical connection between secondary neurulation and the filum terminale has not been discussed in recent embryological studies by clinical neurologists, even those focused on caudal neural tube syndromes [5,6,7]. The first aim of this study, therefore, was to revisit the link between secondary neurulation and the filum terminale during fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…LPs at T12-L1 are too risky to recommend on a routine basis, because a substantial part of the CM would be present within the LP window, even upon adoption of the LDP. As the FT can contain neuronal tissue (Gaddam et al, 2012), we also considered positional shifts of the FT at these three disc levels to evaluate the theoretical risk of its injury if a high LP were to be considered. We found that in hypothetical cases where the CM terminates at a high level, and where the FT might be positioned at the three disc levels under consideration, all theoretical LPs would be safe because the FT is thin and it would also shift sufficiently away from the midsagittal plane upon adoption of the LDP (Tables 5 and 6).…”
Section: Positional Shifts Of the CMmentioning
confidence: 99%